2020
DOI: 10.1186/s12905-020-01059-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the use of modern contraceptive in Nigeria: a multilevel logistic analysis using linked data from performance monitoring and accountability 2020

Abstract: Background The population of Nigeria is estimated at over 190 million and it is projected to increase by 44% between 2015 and 2030. However, less than one-quarter of women within reproductive age in Nigeria uses modern contraceptive methods despite its importance. Hence, this study aims at examining the influence of individual and community level factors on the use of modern contraceptive method. Methods The study is a secondary analysis of linked household and Service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 18 publications
20
35
1
Order By: Relevance
“…We found that modern contraceptive utilization was higher among younger women than older women, which agrees prior study (30). We also saw that educational attainment of woman affects modern contraceptive usage, with better uptake among those who attended high school compared to women with no education or primary school, this was in line with other research (30)(31)(32)(33)(34)(35). Furthermore, the odds of modern contraceptive usage raised along woman's parity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that modern contraceptive utilization was higher among younger women than older women, which agrees prior study (30). We also saw that educational attainment of woman affects modern contraceptive usage, with better uptake among those who attended high school compared to women with no education or primary school, this was in line with other research (30)(31)(32)(33)(34)(35). Furthermore, the odds of modern contraceptive usage raised along woman's parity.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the odds of modern contraceptive usage raised along woman's parity. The uptake of modern contraceptives was considerably greater among women with higher parity contrasted with those who were yet to have a child, this was similar to prior studies (30,32,(35)(36)(37).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is not a good report for primary health facilities because they are closer to the grassroots people and the first point of call for FP and other medical services. The implication of this is the poor FP services, regular stockouts, and low uptake of contractive in rural areas of the country [19,[29][30][31][32][33]. The few facilities that had trained staff on FP commodities logistics did not have sufficient trained staff with an average of 1-2 and 3-4 trained personnel in both primary and secondary healthcare facilities respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This good knowledge was obtained from the amount of information that participants had about the LTRC contraceptive method, from health workers, the media and their friends. There is a significant influence between the level of education, information and support from the social environment on the use of modern contraceptives (Alo, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%